Acquisition of Experts’ Opinions to Explore the Drivers of Business Success in the Construction Industry - Zahidy, Abd-Hamid; Noor Azlinna, Azizan; Sorooshian, Shahryar (2015)
Evidence has pointed that the construction industry is a key sector of every nation’s economic growth. However, a nation can only fully benefited from the stimulus that the construction activities brought to its economy if it has an efficient construction industry (Ofori, 2012). Hence, all activities within the construction industry must be performed effectively and efficiently. One way to achieve this is by ensuring the success of entrepreneurs who run the construction business because they are the key players in the industry. Hofstrand (2010) asserted that successful entrepreneurs should have a detailed knowledge of the key factors needed for their success. Indeed, discovering which factors or practices lead to business success and which lead to failure is a primary, and as yet unfulfilled, the purpose of business research (Rogoff et al., 2004).